Preparation of Platinum Nanoparticles-Graphene Modified Electrode and Selective Determination of Rutin - Shu-Hong Yu; Guang-Chao Zhao (International Journal of Electrochemistry)
Platinum nanoparticles were electrodeposited on graphene modified glassy carbon electrode to form a modified electrode, and the electrode was characterized with scanning electron microscopy (SEM). At the modified electrode, rutin, a natural flavonoid, shows a couple of well-defined redox peaks, which is corresponded to the reduction and reoxidation of rutin. The electrochemical behaviors of rutin at the electrode were investigated, and the results indicated that the electrode reaction is controlled by adsorption process. Under the optimal conditions, the peak currents of differential pulse voltammetry (DPV) increased linearly with the rutin concentration in the range from 2.0×10−8 to 8.0×10−5 M with a limit of detection of 6.7×10−9 M. The as-prepared electrode was successfully used for the selective determination of rutin in tablet, displaying a potential application of graphene composite modified electrode.